2021
DOI: 10.3390/s21144808
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Machine Learning in the Validation of Commercial Wearable Sensors for Gait Monitoring in Patients: A Systematic Review

Abstract: Gait, balance, and coordination are important in the development of chronic disease, but the ability to accurately assess these in the daily lives of patients may be limited by traditional biased assessment tools. Wearable sensors offer the possibility of minimizing the main limitations of traditional assessment tools by generating quantitative data on a regular basis, which can greatly improve the home monitoring of patients. However, these commercial sensors must be validated in this context with rigorous va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 117 publications
(866 reference statements)
0
14
0
Order By: Relevance
“…The importance of validating wearables to provide accurate results are highlighted by Jourdan et al. [44] , focusing on the role of Machine Learning (ML) techniques in the validation of sensors to monitor gait. They found that in more than half of the considered studies the ground truth is represented by annotations and not by a reference instrument; they also stressed the lack of standard evaluation metrics as well as the inhomogeneity in terms of acquisition context.…”
Section: How To Determine the Measurement Uncertainty Of Wearable Dev...mentioning
confidence: 99%
“…The importance of validating wearables to provide accurate results are highlighted by Jourdan et al. [44] , focusing on the role of Machine Learning (ML) techniques in the validation of sensors to monitor gait. They found that in more than half of the considered studies the ground truth is represented by annotations and not by a reference instrument; they also stressed the lack of standard evaluation metrics as well as the inhomogeneity in terms of acquisition context.…”
Section: How To Determine the Measurement Uncertainty Of Wearable Dev...mentioning
confidence: 99%
“…An alternative to laboratory-based 3D CGA are wearable sensor systems coupled with machine learning analytics [8][9][10][11][12]. These sensor systems use predictive machine learning methods to automatically partition and analyse gait (e.g., foot-contact and foot-off events) from sensor signals (e.g., inertial measurement units (IMUs)) [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to laboratory-based 3D CGA are wearable sensor systems coupled with machine learning analytics [8][9][10][11][12]. These sensor systems use predictive machine learning methods to automatically partition and analyse gait (e.g., foot-contact and foot-off events) from sensor signals (e.g., inertial measurement units (IMUs)) [8][9][10][11][12][13]. These sensor systems are mobile, cost-effective and allow the automation of some tasks that currently require laboratory equipment and skilled knowledge [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations